The mushroom body development and learning ability of adult honeybees are influenced by cold exposure during their early pupal stage - Zhu, Chenyu; Li, Han; Xu, Xinjian; Zhou, Shujing; Zhou, Bingfeng; Li, Xiang; Xu, Hongzhi; Tian, Yuanmingyue; Wang, Yanxin; Chu, Yu; Zhang, Xianlan; Zhu, Xiangjie (Frontiers in Physiology, 2023)
The honeybees are the most important pollinator in the production of crops and fresh produce. Temperature affects the survival of honeybees, and determines the quality of their development, which is of great significance for beekeeping production. Yet, little was known about how does low temperature stress during development stage cause bee death and any sub-lethal effect on subsequent. Early pupal stage is the most sensitive stage to low temperature in pupal stage. In this study, early pupal broods were exposed to 20°C for 12, 16, 24, 48 hours, followed by incubation at 35°C until emergence. We found that 48 hours of low temperature duration cause 70% of individual bees to die. Although the mortality at 12 h and 16 h seems not very high, the association learning ability of the surviving individuals was greatly affected. The brain slices of honeybees showed that low temperature treatment could cause the brain development of honeybees to almost stop. Gene expression profiles between low temperature treatment groups (T24, T48) and the control revealed that 1267 and 1174 genes were differentially expressed respectively. Functional enrichment analysis of differentially expressed genes showed that the differential expression of Map3k9, Dhrs4 and Sod-2 genes on MAPK and peroxisome signaling pathway caused oxidative damage to the honeybee head. On the FoxO signal pathway, InsR and FoxO were up-regulated, and JNK, Akt and Bsk were down-regulated; and on the insect hormone synthesis signal pathway, Phm and Spo genes were down-regulated. Therefore, we speculate that low temperature stress affects hormone regulation. It was detected that the pathways related to the nervous system were Cholinergic synapse, Dopaminergic synapse, GABAergic synapse, Glutamatergic synapse, Serotonergic synapse, Neurotrophin signaling pathway, and Synaptic vesicle cycle. This implies that the synaptic development of honeybees is quite possibly greatly affected by low temperature stress. Understanding how low temperature stress affects the physiology of bee brain development and how it affects bee behavior provide a theoretical foundation for a deeper comprehension of the temperature adaptation mechanism that underlies the "stenothermic" development of social insects, and help to improve honeybee management strategies to ensure the healthy of colony.